Colchicine in Cardiovascular Disease: In-Depth Review. Issue 1 (4th January 2022) - Deftereos, Spyridon G.; Beerkens, Frans J.; Shah, Binita; Giannopoulos, George; Vrachatis, Dimitrios A.; Giotaki, Sotiria G.; Siasos, Gerasimos; Nicolas, Johny; Arnott, Clare; Patel, Sanjay; Parsons, Mark; Tardif, Jean-Claude; et al.
Abstract : Inflammation plays a prominent role in the development of atherosclerosis and other cardiovascular diseases, and anti-inflammatory agents may improve cardiovascular outcomes. For years, colchicine has been used as a safe and well-tolerated agent in diseases such as gout and familial Mediterranean fever. The widely available therapeutic has several anti-inflammatory effects, however, that have proven effective in a broad spectrum of cardiovascular diseases as well. It is considered standard-of-care therapy for pericarditis, and several clinical trials have evaluated its role in postoperative and postablation atrial fibrillation, postpericardiotomy syndrome, coronary artery disease, percutaneous coronary interventions, and cerebrovascular disease. We aim to summarize colchicine's pharmacodynamics and the mechanism behind its anti-inflammatory effect, outline thus far accumulated evidence on treatment with colchicine in cardiovascular disease, and present ongoing randomized clinical trials. We also emphasize real-world clinical implications that should be considered on the basis of the merits and limitations of completed trials. Altogether, colchicine's simplicity, low cost, and effectiveness may provide an important addition to other standard cardiovascular therapies. Ongoing studies will address complementary questions pertaining to the use of low-dose colchicine for the treatment of cardiovascular disease.